Modeling MyD88 Deficiency In Vitro Provides New Insights in Its Function - Craig-Mueller, Nils; Hammad, Ruba; Elling, Roland; Alzubi, Jamal; Timm, Barbara; Kolter, Julia; Knelangen, Nele; Bednarski, Christien; Gläser, Birgitta; Ammann, Sandra; Ivics, Zoltán; Fischer, Judith; et al. (Frontiers in Immunology, 2020)
Inherited defects in MyD88 and IRAK4, two regulators in Toll-like receptor (TLR) signaling, are clinically highly relevant but still incompletely understood. MyD88 and IRAK4-deficient patients are highly susceptible to a narrow spectrum of pathogens, with ∼50% lethality in the first years of life. To better understand the underlying molecular and cellular characteristics that determine disease progression, we aimed at modeling the cellular response to pathogens in vitro. To this end, we determined the immunophenotype of monocytes/macrophages derived from MyD88 and IRAK4-deficient patients. We recognized that macrophages derived from both patients were poorly activated by streptococci, indicating that both signaling intermediates are essential for the immune response to facultative pathogens. To characterize this defect in more detail, we generated induced pluripotent stem cells (iPSCs) of fibroblasts derived from an MyD88-deficient patient. The underlying genetic defect was corrected using Sleeping Beauty transposon vectors encoding either the long (L) or the short (S) MYD88 isoform, respectively. Macrophages derived from these iPSC lines (iMacs) expressed typical macrophage markers, stably produced either MyD88 isoform, and showed robust phagocytic activity. Notably, iMacs expressing MyD88-L, but not MyD88-S, exhibited similar responses to external stimuli, including cytokine release pattern, as compared to genetically normal iMacs. Thus, the two MyD88 isoforms assume distinct functions in signaling. In conclusion, iPSC technology, in combination with efficient myeloid differentiation protocols, provides a valuable and inexhaustible source of macrophages which can be used for disease modeling. Moreover, iPSC-derived macrophages may eventually aid in stabilizing MyD88-deficient patients during pyogenic infections.